(untitled) (London Journal of Medical and Health Research, 2025)
Part IV of the article includes many sections of Palliative and Integrative care. It provides many sources on how to use this type of care. For example, the information is about guidelines and case studies on how to implement and assess the treatments, and goals for the patients’ care. Also mentioned are, the five stages of palliative care, The Pillars and Principles of Palliative care and Palliative Care Guidelines Practice Guidelines for Quality Palliative Care.